Representações e práticas profissionais de pedagogas formadas em serviço pela UFPB - Campêlo, Maria da Conceição Miranda (2008)
The following work's intention is to describe and analyze a qualitative research in the field of Master's Degree's Education. This research has as its objective to identify and analyze the contributions offered by the teacher's formation policy to improve the Pedagogy graduate's (and former members of PEC/RP) professional practices. The theoretical basis used on this study was built around the works of Serge Moscovici and other authors such as Libâneo, Tardif, and Nóvoa. They, among others, discuss the teacher's formation policies and how these reflect on their professional practice. Using the ethnographical approach on education, we utilized active observation, semi-structured interviews and polls as our data collection instruments. Through those we searched for the graduate's social representations of some topics such as: teacher-student relationship; planning of pedagogical activities; teaching dynamics; evaluation processes and conceptions about initial and continuing formation. This way, we also looked at the opinions of the school's technical and administrative staff about the work of the graduates. The data collection was done during the progress of the research, which in turn lasted four (04) months. The research process included weekly visits to public schools where the graduates and former members of PEC/RP were teaching. The data collection instruments allowed us to better associate the data to the subjects of the research; the teachers shared their feelings, behavior, ideas, opinions and histories about their professional practices and the social representations of elementary school. We believe that our research reached the point of establishing a real connection between the researchers and the graduate teachers. That connection is being used to show how much the contributions PEC/RP has made have influenced in the construction of a new practice to be used in the classroom. This practice seeks to imbue in the newly-formed professional notions of respect, discipline, listening, social and politic awareness, not leaving behind empathy and friendship between peers.